Influence of dietary fibers on the bioaccessibility of glucose released from rice during dynamic in vitro gastrointestinal digestion - Fernandes, Jean Michel (2019)
The authors would like to thank the investment project nº 017931 – Development of rice products with low glycemic index- co-funded by Fundo Europeu de Desenvolvimento Regional (FEDER) through Programa Operacional Competitividade e Internacionalização (COMPETE 2020). Ana C. Pinheiro would like to also acknowledge the Foundation for Science and Technology (FCT) for their fellowship (SFRH/BPD/101181/2014). This work was supported by Portuguese Foundation for Science and Technology (FCT) under the scope of the strategic funding of UID/BIO/04469/2013 unit, and COMPETE 2020 (POCI-01-0145-FEDER-006684) and BioTecNorte operation (NORTE-01-0145-FEDER-000004) funded by the European Regional Development Fund under the scope of Norte2020 - Programa Operacional Regional do Norte.